The effectiveness of the Aggression Replacement Training (ART) model to reduce the aggressive level of madrasah aliyah students - Ali Murtadho; Syed Muzaffar Hussain; Raden Azamry Raden Perhan; Ibrahim Bin Ahmad (Journal of Advanced Guidance and Counseling, 2022)
Purpose: This study aims to prove the effectiveness of Aggression Placement Training ( ART ) in reducing the aggressiveness of students, especially in Islamic High School (Madrasah Aliyah).Method: This research used a true-experimental design method with a randomized pretest-posttest control group design. Samples were determined using random selection technique. The subjects were students of class XI Madrasah Aliyah Negeri Kendal. Aggressiveness data collection is using the Buss-Perry Aggression Questionnaire (BPAQ).Results: The results of the study revealed that ART with an Islamic cultural and religious approach was effective in reducing the level of students' aggressiveness. The data show the level of aggressiveness of students in the experimental group was significantly lower than students in the control group. The theoretical means of 93,461 to 45.09 with a significance level of 0.00.Implication: ART is suggested to be applied to overcome student’s aggression, therefore it is recommended for further researchers to use larger research subjects to have a more accurate conclusion; use ART for problems other than aggression such as low prosocial, low morale, and so on; conduct research in school settings where students are more heterogeneous, which is using ART to reduce the level of students aggression in senior high school or vocational high school.Originally: This study used ART that had been adapted to the conditions of the Indonesian people, especially those who were Muslim. The training related to skill streaming, anger control training (ACT), and moral reasoning had an Islamic nuance.***Tujuan - Penelitian ini bertujuan untuk membuktikan efektifitas Pelatihan Penempatan Agresi ( ART ) dalam mengurangi agresivitas siswa khususnya di Madrasah Aliyah .Metode - Penelitian ini menggunakan metode true-experimental design dengan rancangan randomized pretest-posttest control group design. Sampel ditentukan dengan teknik pemilihan acak. Subjek penelitian adalah siswa kelas XI Madrasah Aliyah Negeri Kendal. Pengumpulan data agresivitas menggunakan Buss-Perry Aggression Questionnaire (BPAQ).Hasil - Hasil penelitian mengungkapkan bahwa ART dengan pendekatan budaya dan agama Islam efektif dalam menurunkan tingkat agresivitas siswa. Data menunjukkan tingkat agresivitas siswa pada kelompok eksperimen secara signifikan lebih rendah dibandingkan siswa pada kelompok kontrol. Rerata teoritis sebesar 93,461 sampai dengan 45,09 dengan taraf signifikansi 0,00.Implikasi - ART disarankan untuk diterapkan untuk mengatasi agresi siswa, oleh karena itu disarankan bagi peneliti selanjutnya untuk menggunakan subjek penelitian yang lebih besar untuk mendapatkan kesimpulan yang lebih akurat; menggunakan ART untuk masalah selain agresi seperti prososial rendah, moral rendah, dan sebagainya; melakukan penelitian di lingkungan sekolah yang siswanya lebih heterogen, yaitu penggunaan ART untuk mengurangi tingkat agresi siswa di sekolah menengah atas atau sekolah menengah kejuruan.Orisinalitas -  Penelitian ini menggunakan ART yang sudah disesuaikan dengan kondisi masyarakat Indonesia, khususnya yang beragama Islam. Pelatihan terkait skill streaming, pelatihan pengendalian amarah (ACT), dan penalaran moral bernuansa islami.